answersLogoWhite

0


Best Answer

4z + 820 is not an equation. It has no answer, because it asks no question.

User Avatar

Wiki User

โˆ™ 2012-03-25 00:40:39
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1020 Reviews

Add your answer:

Earn +20 pts
Q: What is the answer to the equation 4z plus 820?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the answer to -8z plus 12 equals 12 - 4z?

-8z + 12 = 12 - 4z-8z +4z + 12 = 12 - 4z +4z-4z + 12 -12 = 12 -12-4z / -4 = 0 / -4z = 0:)


What is 4z plus 2 plus 5z-3?

4z + 2 + 5z - 3 = 9z - 1


What is 7 plus 4z equals 43?

7 + 4z = 437 + 4z -7 = 43 - 7 4z = 43 - 7 4z = 36 z = 9


11z plus 4z squared plus 10zsquared?

11z+√(4z)+√(10z)=11z+√(10z)+2*√(z)


What is q equals 4m plus 4z solving for M?

To solve for this, you need to isolate "m." To accomplish this, subtract 4m from both sides of the equation. This should change the equation to q - 4z = 4m. Then you divide both sides by 4, getting q/4 - 4z/4 = m. After completing the division, you should get 1/4q - z = m.


What is 9x plus 3y plus 5z - 5x plus 4z-7y?

9x + 3y + 5z - 5x + 4z - 7y = 4x - 4y + 9z


4z plus 8-6 is what?

34


How do you prove Equation -6z plus 2 equals 3z plus 4z plus 28 solved for z z equals -2?

-6z + 2 = 3z + 4z + 28 Add 6z to both sides: 2 = 3z + 4z + 28 + 6z = 28 + 13z Subtract 28 from both sides: - 26 = 13z Divide both sides by 13: -2 = z


How do you solve 4z plus 3 equals 6 plus 2z?

4z + 3 = 6 + 2zSubtract 2z from each side of the equation:2z + 3 = 6Subtract 3 from each side:2z = 3Divide each side by 2:z = 3/2 = 1.5


What is 4z to the forth power plus 64z squared?

4z squared (z+4) (z+4)


-6z plus 2 equals 3z plus 4z plus 28 How do you prove the answer -2 is correct?

-6z 2 = 3z+ 4z+28 -6z+2 +3z = 3z+ 4z +28 +4z -6z+4z+2 = 3z+ 28 -10z+2 -3z= 28 - 2 -10z + -3z = 26 -13z/13 = 26/-13 z = -2


Use the Gauss-Jordan method to solve the equation 3x-5y-2z -9 -4x plus 3y plus z 11 8x-5y plus 4z 6?

Without an equality sign the given terms can't be considered to be an equation.

People also asked